Pengaruh Ukuran Perusahaan, Profitabilitas, dan Leverage Terhadap Audit Delay (Studi Empiris Perusahaan Perkebunan pada Bursa Efek Indonesia) - Naufaldo Rizki Tanama; Hero Priono (Ekonomis: Journal of Economics and Business, 2023)
This study aims to cover the effect of Firm Size, Profitability, and Leverage on Audit Delay. The secondary data source is the financial reports of plantation sector companies in 2017-2021. This type of research uses a quantitative approach. The data analysis technique is a Partial Least Square (PLS) approach. The results of the study prove that (1) Firm size has no effect on audit delay, (2) Profitability has no effect on audit delay, (3) Leverage has an effect on audit delay.